Mechanical evaluation of mandibular fractures stabilized with absorbable implants or intraoral splints in cats - Castejon-Gonzalez, Ana C.; Friday, Chet S.; Hast, Michael W.; Reiter, Alexander M. (Frontiers in Veterinary Science, 2025)
IntroductionThe goal of this cadaver study in cats was to compare the mechanical properties of intact mandibles (C) with mandibles whose simulated fracture was located between the third and fourth premolar teeth and repaired with four possible treatments: (1) Stout multiple loop interdental wiring plus bis-acryl composite intraoral splint (S); (2) modified Risdon interdental wiring plus bis-acryl composite intraoral splint (R); (3) ultrasound-aided absorbable fixation plate (P); and (4) ultrasound-aided absorbable fixation mesh (M).Materials and methodsThirty feline mandibles were randomly assigned to the control and treatment groups. Mandibles were loaded by cantilever bending on the canine tooth, first in non-destructive cyclic loading followed by destructive ramp-to-failure loading.ResultsCyclic loading showed no differences between the treatment groups in angular deflection (a measure of sample flexion under non-destructive loads); however, the R group had significantly higher angular deflection than the C group. In destructive testing, no differences in mechanical properties were found between the treatment groups; however, all treatment groups demonstrated significantly lower maximum bending moment, bending stiffness, energy to failure, and maximum force when compared to the control group. The main mode of failure of the intraoral splint groups (S and R) was fracture of the bis-acryl composite (50%), and the main mode of failure of the absorbable fixation groups (P and M) was fracture of the pins (91.7%).DiscussionIntraoral splint and absorbable fixation methods have low strength and stiffness. The four treatments tested provided similar stabilization of mandibular fractures located between the third and fourth premolar teeth.